2022
DOI: 10.1186/s43170-021-00069-0
|View full text |Cite
|
Sign up to set email alerts
|

Areawide management of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), using selected cover crop plants

Abstract: Background Fall armyworm, Spodoptera frugiperda (J. E. Smith) is a migratory moth that annually migrates northward each spring from sites in southern Florida and southern Texas. This caterpillar pest feeds on and damages row, turf and vegetable crops in the eastern and central U.S. Before migrating in spring, it feeds on cover crops in central and eastern Florida and expands its populations. Our objective was to use multi-year studies to compare fall armyworm populations that develop in cover c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Cover crops were planted at the University of Florida (UF) North Florida Research and Education Center, Quincy, Florida in 2011 and 2012 (Gadsden county; 30.5460000 °N, 84.5990000 °W), and at the UF/IFAS (Institute of Food and Agricultural Sciences) Plant Science Research and Education Unit, Citra, Florida in 2012 and 2013 (Marion county; 29.4100000 °N, 82.1730000 °W). These plots were the same ones used for the fall armyworm infestation trials (Meagher et al 2022). Briefly, the experimental design at both locations was a randomized complete block with 4 cover crop treatments, 4 blocks, and 6–12 row plots that were 15.24–30.50 m long and were planted on 91.4 cm row centers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cover crops were planted at the University of Florida (UF) North Florida Research and Education Center, Quincy, Florida in 2011 and 2012 (Gadsden county; 30.5460000 °N, 84.5990000 °W), and at the UF/IFAS (Institute of Food and Agricultural Sciences) Plant Science Research and Education Unit, Citra, Florida in 2012 and 2013 (Marion county; 29.4100000 °N, 82.1730000 °W). These plots were the same ones used for the fall armyworm infestation trials (Meagher et al 2022). Briefly, the experimental design at both locations was a randomized complete block with 4 cover crop treatments, 4 blocks, and 6–12 row plots that were 15.24–30.50 m long and were planted on 91.4 cm row centers.…”
Section: Methodsmentioning
confidence: 99%
“…Cowpea is a warm-season annual legume that alone or mixed with sorghum-sudangrass can be used as a cover crop or intercrop with vegetables (Cho et al 2012; Harrison et al 2014). More comprehensive studies after Meagher et al (2004) showed sunn hemp and cowpea had fall armyworm populations 70–96% less than sorghum-sudangrass (Meagher et al 2022), concluding that substituting sorghum-sudangrass with these plants could be preferable as a replacement cover crops for areawide management of fall armyworm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has emerged as one of the most important global polyphagous pests of crops [ 20 , 21 ]. FAW is a serious concern in various agroecosystems and can feed on most of the cover and cash crops [ 22 , 23 ]. The management of FAW in recent years has ranged from the use of synthetic pesticides to biopesticides, cultural control, and biological control [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since its invasion in all tropical and subtropical regions of the world, the FAW has attracted increasing research interest to find sustainable management options through agroecological practices and the use of biopesticides (Bateman et al, 2018; Harrison et al, 2019; Midega et al, 2018). In the Americas, producers and researchers have long studied FAW and their experiences are being used to develop sustainable management options appropriate for large‐scale farmer systems (Meagher et al, 2022; Sparks, 1986). For example, in the United States, Brazil and Argentina, FAW was commonly controlled by the application of effective pesticides and the use of genetically modified corn (Bt corn), which incorporated genes to produce lethal toxins against FAW (Hruska, 2019).…”
Section: Introductionmentioning
confidence: 99%